Effect of silane coupling agent on bond improvement of urea formaldehyde resin in wheat straw particleboard - Seaid Masoumeh Hafezi (Regional Information Center for Science and Technology (RICeST), 2014)
This research was conducted to investigate the effect of silane coupling agent usage to improve the bond formation of urea formaldehyde resin in wheat straw particleboard production. Three levels (0.5% and 10%; based on the dry weight of the resin) of silane coupling agent and 10% urea formaldehyde resin were used to produce one layer particle boards with 16mm nominal thickness. Physical and mechanical properties including MOR, MOE, IB and thickness swelling (after 2 and 24 hours immersion in water) were measured. The results of this study showed that adding silane coupling agent to the resin in wheat straw particleboard production, increased MOR, MOE and IB and dimensions stability improved. Optimum dosage for silane coupling agent to improve modulus of elasticity, internal bonding and thickness swelling was 10% and the for modulus of rupture, it was determined as 5%.